Synergistic effect of LIPUS and its application in oral cavity - ZHAO Piao, GUAN Xiaoyan, LIU Jianguo, XIANG Mingli, XIAO Linlin (Kouqiang yixue)
Low-intensity pulsed ultrasound(LIPUS)was first introduced in clinic for the treatment of fracture because of its safety, effectiveness and non-trauma. Then, a large number of subsequent studies have used LIPUS as a synergistic factor in bone, cartilage, joint, cancer treatment and oral clinical research, jointly revealing the powerful synergistic effect of LIPUS. This paper summarizes the synergistic effect of LIPUS in the above research fields, in order to broaden the possible clinical application scope of LIPUS.